The professional : a spenser mystery - Parker, Robert B., 1932-2010 (A Spenser mystery, 2010)
Spenser has never had any difficulty handling women. But when four stunningly beautiful trophy wives hire him to protect them against a blackmailer threatening to expose their infidelities, even he must admit that they look like trouble. For a private eye of Spenser's abilities and contacts, tracking down Gary Eisenhower, the blackmailer and serial adulterer, isn't too difficult - but almost in spite of himself Spenser finds that he quite likes the guy. Certainly the women, with their loose purse-strings and looser morals, and their loveless marriages to rich, powerful, corrupt men, are hard to feel sorry for. But a killing soon changes the complexion of the case, and draws Spenser into the world of Boston's monied aristocracy: a world of corruption, vice and murder. As the bodies start to pile up, Spenser must decide which of his friends he can trust.